Plant diversity and grasses increase root biomass in a rainfall and grassland diversity manipulation - Podzikowski, Laura Y.; Heffernan, Megan M.; Bever, James D. (Frontiers in Ecology and Evolution, 2023)
The loss of plant productivity with declining diversity is well established, exceeding other global change drivers including drought. These patterns are most clearly established for aboveground productivity, it remains poorly understood whether productivity increases associated with diversity are replicated belowground. To address this gap, we established a plant diversity-manipulation experiment in 2018. It is a full factorial manipulation of plant species richness and community composition, and precipitation. Three and five years post-establishment, two bulk soil cores (20cm depth) were collected and composited from each plot and were processed for roots to determine belowground biomass as root standing crop. We observed a strong positive relationship between richness and aboveground production and belowground biomass, generating positive combined above and belowground with diversity. Root standing crop increased 1.4-fold from years three to five. Grass communities produced more root biomass (monoculture mean 463.9 ± 410.3 g m-2), and the magnitude of the relationship between richness and root standing crop was greatest within those communities. Legume communities produced the fewest roots (monoculture mean 212.2 ± 155.1 g m-2), and belowground standing crop was not affected by diversity. Root standing crops in year three were 1.8 times higher under low precipitation conditions, while in year five we observed comparable root standing crops between precipitation treatments. Plant family was a strong mediator of increased belowground biomass observed with diversity, with single family grass and aster families generating 1.7 times greater root standing crops in six compared to single species communities, relationships between diversity and aboveground production were consistently observed in both single-family and multiple family communities. Diverse communities with species from multiple families generated only 1.3 times the root standing crop compared to monoculture average root biomass. We surprisingly observe diverse single family communities can generate increases in root standing crops that exceed those generated by diverse multiple family communities, highlighting the importance of plant richness within plant family for a given community. These patterns have potential implications for understanding the interactions of multiple global change drivers as changes in both precipitation and plant community composition do alter whether plant production aboveground is translated belowground biomass.